The effect of pregnant women’s compliance levels on their satisfaction with antenatal care - Asmah Sukarta; Parmiati Parmiati; Hamdiyah Hamdiyah (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Pregnancy is a physiological process, yet it requires special care and services to ensure the safety of both the mother and the baby. A mother’s adherence to attending antenatal care (ANC) visits refers to her compliance with the recommended health care visits, in accordance with established standards. Satisfaction reflects how satisfied patients are with the care they receive; patients tend to react positively when care meets their expectations. Conversely, they tend to express dissatisfaction if services do not meet the standards they anticipate. Purpose: To determine the effect of pregnant women’s compliance levels on satisfaction with antenatal care services. Method: This was a cross-sectional study conducted from December 1, 2025, to December 30, 2026, in the service area of the Bontomatene Community Health Center involving 30 pregnant women as the sample. A purposive sampling technique was used, and a questionnaire was administered. Results: Based on the study results regarding the influence of pregnant women’s compliance levels on satisfaction with antenatal care services, the statistical test yielded a p-value of 0.000 < 0.05, indicating that there is an influence of pregnant women’s compliance levels on satisfaction with antenatal care services at the Blud. Conclusion: There is an effect of the level of compliance of pregnant women on satisfaction with antenatal care services at the Blud, with a p-value of 0.000 < 0.05 Suggestion: It is hoped that the results of this study will enhance the knowledge of all respondents, particularly regarding the level of compliance among pregnant women and their satisfaction with antenatal care services.